Tyrosol induces multiple drug resistance in yeast Saccharomyces cerevisiae - Noskova, Elizaveta O.; Markova, Olga V.; Knorre, Dmitry A.; Galkina, Kseniia V. (Frontiers in Microbiology, 2023)
In yeast, multiple (pleiotropic) drug resistance (MDR) transporters efflux xenobiotics from the cytoplasm to the environment. Additionally, upon the accumulation of xenobiotics in the cells, MDR genes are induced. At the same time, fungal cells can produce secondary metabolites with physico-chemical properties similar to MDR transporter substrates. Nitrogen limitation in yeast Saccharomyces cerevisiae leads to the accumulation of phenylethanol, tryptophol, and tyrosol, which are products of aromatic amino acid catabolism. In this study, we investigated whether these compounds could induce or inhibit MDR in yeast. Double deletion of PDR1 and PDR3 genes, which are transcription factors that upregulate the expression of PDR genes, reduced yeast resistance to high concentrations of tyrosol (4–6 g/L) but not to the other two tested aromatic alcohols. PDR5 gene, but not other tested MDR transporter genes (SNQ2, YOR1, PDR10, PDR15) contributed to yeast resistance to tyrosol. Tyrosol inhibited the efflux of rhodamine 6G (R6G), a substrate for MDR transporters. However, preincubating yeast cells with tyrosol induced MDR, as evidenced by increased Pdr5-GFP levels and reduced yeast ability to accumulate Nile red, another fluorescent MDR-transporter substrate. Moreover, tyrosol inhibited the cytostatic effect of clotrimazole, the azole antifungal. Our results demonstrate that a natural secondary metabolite can modulate yeast MDR. We speculate that intermediates of aromatic amino acid metabolites coordinate cell metabolism and defense mechanisms against xenobiotics.